2019
DOI: 10.1038/s41390-019-0468-7
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating and maintaining spontaneous breathing during transition of preterm infants

Abstract: Most preterm infants breathe at birth, but need additional respiratory support due to immaturity of the lung and respiratory control mechanisms. To avoid lung injury, the focus of respiratory support has shifted from invasive towards non-invasive ventilation. However, applying effective non-invasive ventilation is difficult due to mask leak and airway obstruction. The larynx has been overlooked as one of the causes for obstruction, preventing face mask ventilation from inflating the lung. The larynx remains mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 147 publications
0
16
0
2
Order By: Relevance
“…After birth the primary site of gas exchange shifts to the lungs, after which oxygenation is largely determined by the surface area available for gas exchange, the gas diffusion distance and the partial pressure gradient for oxygen between the alveoli and adjacent capillaries. Thus, oxygenation depends on adequate lung aeration (surface area), gas diffusion distance and the amount of additional oxygen given during neonatal support (partial pressure gradient), all of which are largely dependent on the success of neonatal transition especially in preterm infants ( 7 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After birth the primary site of gas exchange shifts to the lungs, after which oxygenation is largely determined by the surface area available for gas exchange, the gas diffusion distance and the partial pressure gradient for oxygen between the alveoli and adjacent capillaries. Thus, oxygenation depends on adequate lung aeration (surface area), gas diffusion distance and the amount of additional oxygen given during neonatal support (partial pressure gradient), all of which are largely dependent on the success of neonatal transition especially in preterm infants ( 7 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm born infants often fail to aerate their immature lungs and need respiratory support in order to transition from a foetus into a neonate. The success of transition is usually reflected by heart rate and pulmonary gas exchange efficiency, which is largely determined by the gas exchange surface area of the lungs and the gas diffusion distance, and is reflected by the need for altering the alveolar oxygen gradient (7,8). Currently, there are various versions of an oxygenation index (OI) used to identify hypoxic respiratory failure in neonates and paediatric patients (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Bei Frühgeborenen kann bereits ein übermäßiger Druck mit der Maske auf das Gesicht eine effektive Beatmung behindern. Auch eine Engstellung des Larynx kann bei diesen möglicherweise die Ursache für eine insuffiziente Beatmung sein [ 10 , 155 , 156 , 194 ].…”
Section: Wissenschaftliche Grundlagen Auf Deren Basis Die Empfehlungen Für Die Praxis Zur Versorgung Und Reanimation Des Neugeborenen Berunclassified
“…Dieses kritische Ereignis löst eine Folge voneinander abhängiger kardiopulmonaler Veränderungen aus, die den Übergang zum extrauterinen Leben ermöglichen [9]. Spontane Atemanstrengungen (Unterdruck) oder eine weniger effektive künstliche Beatmung (Überdruck) sind unerlässlich, um den notwendigen transpulmonalen Druck zu erzeugen, der erforderlich ist, um die mit Flüssigkeit gefüllte Lunge zu belüften, und eine adäquate funktionelle Residualkapazität herzustellen und aufrechtzuerhalten [10,11]. Die meisten, aber nicht alle Neugeborenen erleben diese Anpassungspha-se an das extrauterine Leben völlig ohne Probleme.…”
Section: Anpassung An Das Leben Nach Der Geburtunclassified
“…The effectiveness of non-invasive support is dependent on infants having a patent airway since the larynx of newborn infants closes during apnea (4)(5)(6)(7)(8). As the larynx only opens during a breath, support at birth now focuses on stimulating and supporting spontaneous breathing (9). Recent studies showed that breathing effort can be stimulated by adequate oxygenation, repetitive tactile stimulation and caffeine (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%